Implementation of the strategy of international cooperation for the wide and continuous promotion of the rich cultural heritage of our country (specifically in the field of music and theatre) at the international level - Alimirzoyeva, Yagut; Mehtizada, Ragsana; Jafarov, Rukhsara (ADA University, 2022)
The study of the potential for the development of national cultures, global cultural processes, intercultural exchanges, and links has always been critical. These challenges, however, have grown much more critical in our modern period, which is marked by the increase of political, economic, and cultural relations between peoples, nations, and countries, as well as the strengthening of globalization and integration processes. There is no civilization on Earth that is distinct from its national origins and hues. Simultaneously, it is hard to envisage national cultures developing in isolation from global forces. In this context, it is not coincidental that the interplay of national cultures, intercultural communication, the link between national and universal ideals, cultural and civilizational issues, and multiculturalism have recently been hot topics of discussion. Today, the Azerbaijani state is deeply active in global cultural collaboration. The fact that our country recently hosted several important international cultural and humanitarian events demonstrates how much our state values intercultural interaction. Today, our national culture is a critical aspect in determining if our country is deserving of a place in the civilized world. Our culture's strategic potential enables us to integrate into the global cultural community while retaining our traditional national identity.
Keywords: National culture -- Development.; Global cultural processes.; Intercultural exchanges.; Public and International Affairs